Estimating individual physical capability (IPC) to make journeys by bicycle. Issue 5 (28th May 2018) - Philips, Ian; Watling, David; Timms, Paul
ABSTRACT: We propose a novel method to estimate capability to make bicycle journeys, specifically considering the individual physical capability (IPC) of entire populations of individuals from all population segments of an area, not just current cyclists. IPC considers the physical constraints on the maximum distance people could cycle given the typical topography of where they live (Distance IPC), and then estimates their ability to make a particular journey (Journey IPC). IPC, when estimated in this way for a particular point in time, may be informed by antecedent behavioral choices and capabilities, and may be a constraint or enabler of subsequent capabilities, potential adaptations and behavior. The focus of the present paper is on explaining a generic method of estimating Distance IPC and Journey IPC by constructing an individually based spatially fine-grained model. We show how such an individual-level model may be implemented for a population resident in many small spatial zones by use of spatial micro-simulation (population synthesis), to generate the individual attributes required as inputs to the model. We present a case-study for the city of Leeds, UK. We explain the range of data sources used, explore sensitivity of the results to assumptions of the model, and illustrate the ability of the model to simulate the effects of policies. Finally, we identify several possible application areas and opportunities to further develop the model.